2009
DOI: 10.4014/jmb.0812.675
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression, Purification, and Immunogenicity of Recombinant Porin Proteins of Salmonella enterica Serovar Typhi (S. Typhi)

Abstract: Porin proteins of Gram-negative bacteria are outer membrane proteins that act as receptors for bacteriophages and are involved in a variety of functions like solute transport, pathogenesis, and immunity. Salmonella enterica serovar Typhi (S. Typhi), a Gram-negative bacterium, is the causative agent of typhoid fever. Porins of S. Typhi have been shown to have a potential role in diagnostics and vaccination. In the present study, the major outer membrane proteins OmpF and OmpC from S. Typhi were cloned in pQE30U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…It has been previously reported that, OmpF protein is resistant to high temperature and denaturing agents and preferably expressing at low osmolar conditions (Verma et al, 2009 (47-50, 83-86, 127-130, 258-261, 263-266), single tyrosine kinase phosphorylation site (52-58), N-myristoylation site at nine locations (104-109, 141-146, 154-159, 166-171, 172-175, 194-199, 207-212, 288-293, 305-310), three protein kinase phosphorylation sites (150-152, 158-160, 215-217) and N-glycosylation sites at three locations (184-187, 156-259, 272-275). Antigenic characterization of translated protein sequence was done by VaxiJen v2.0 antigen prediction server (Doytchinova and Flower, 2007) and OmpF protein was found to be antigenic in nature with an overall antigen prediction score of 0.85.…”
Section: Sequence Analysis Of S Typhimurium Ompf Genementioning
confidence: 99%
“…It has been previously reported that, OmpF protein is resistant to high temperature and denaturing agents and preferably expressing at low osmolar conditions (Verma et al, 2009 (47-50, 83-86, 127-130, 258-261, 263-266), single tyrosine kinase phosphorylation site (52-58), N-myristoylation site at nine locations (104-109, 141-146, 154-159, 166-171, 172-175, 194-199, 207-212, 288-293, 305-310), three protein kinase phosphorylation sites (150-152, 158-160, 215-217) and N-glycosylation sites at three locations (184-187, 156-259, 272-275). Antigenic characterization of translated protein sequence was done by VaxiJen v2.0 antigen prediction server (Doytchinova and Flower, 2007) and OmpF protein was found to be antigenic in nature with an overall antigen prediction score of 0.85.…”
Section: Sequence Analysis Of S Typhimurium Ompf Genementioning
confidence: 99%
“…The recombinant OmpC (rOmpC) and recombinant OmpF (rOmpF) were prepared according to Verma et al (2009). The ompC and ompF genes were amplified by PCR and cloned in pQEUA vector.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that OmpC of S. Typhimurium folds in a similar way as OmpF of E. coli and OmpC of S. Typhi (Arockiasamy et al, 2004b;Kumar and Krishnaswamy, 2005). The expression of OmpC during infection (Puente et al, 1989;Verma et al, 2009) and its capacity to display heterologous epitopes on the cell surface (Puente et al, 1995) make it an important candidate antigen with potential applications in immunology and vaccine design. Studies using Salmonella porin specific monoclonal antibodies (Muthukkaruppan et al, 1992) showed that S. Typhi OmpC is the major surface antigen with unique exposed epitopes.…”
Section: Challenge Studiesmentioning
confidence: 99%
“…Maximum survival was seen in the animals immunized with 49 kDa protein (100%), followed by 37 kDa (66.7%), 33 kDa (50%) and 15kDa (33.3%) (Hamid and Jain, 2008). Verma et al (2009) evaluated the immunogenicity of the recombinant porins, in Swiss albino mice with three different adjuvants. In contrast to OmpF, the high titer (p < 0.05) of recombinant OmpCspecific IgG antibody was observed in mice immunized with aluminium hydroxide gel followed by Freund's adjuvant and montanide.…”
Section: Challenge Studiesmentioning
confidence: 99%
See 1 more Smart Citation